The Optimalization of Zakah Distribution During Covid-19 Pandemic Using Data Envelopment Analysis (DEA) Method at Badan Amil Zakat Nasional (BAZNAS) Indonesia - Yosi Maytesa; Mega Ilhamiwati (AL-FALAH : Journal of Islamic Economics, 2021)
Purpose: The purpose of this paper is to assess the level of optimality of zakat institutions to deal with the economic crisis during the Covid-19 pandemic.Design/Method/Approach: In this research, the measurement of efficiency of zakat distribution during the Covid-19 pandemic at badan amil zakat nasional (BAZNAS) has been carried out using data envelopment analysis (DEA) method.Findings: The result is the mean of zakah distribution relative efficiency are 70 %. Finally, some suggestion for evaluating the distribution of zakat in the future has been discussed. Originality/Values: The contribution of this research is to obtain the efficiency value of zakat distribution during the Covid-19 pandemic. So that with the result, the management of zakat distribution at BAZNAZ can improved and evaluated.